Communication Dynamics and Adaptation Process in Cassava Chain Optimization Among Peasant Farmers in Obio/Akpor, Rivers State. - OLUWATOBI, Ajoke Oyedele; IHEJIRIKA, Walter Chikwendu; NWACHUKWU, Fautinus Ginikanwa (International Journal of English Language & Communication Studies, 2024)
This study is an examination of the communication dynamics and adaptation process in cassava chain optimization among peasant farmers in Obio/Akpor, Rivers State. The theoretical framework adopted in the study was the diffusion of innovation theory. The research design for this study adopted a qualitative method, specifically utilizing in-depth interviews to gather in-depth information from participants. The population for this study consists of peasant cassava farmers in Obio/Akpor, Rivers State, Nigeria, who are involved in both cassava farming and processing activities, which stood at 156. A sample size of 6 peasant cassava farmers was selected to provide a manageable yet diverse pool of participants, offering insights into the varying degrees of knowledge and attitude toward modern farming techniques. The sampling technique employed was purposive sampling, where farmers who have been involved in cassava farming for at least five years and have a production capacity that qualifies them as peasant are chosen. Data collection was conducted through semi-structured email interviews. For data analysis, thematic analysis was employed to identify patterns and themes from the farmers’ responses. The qualitative data were coded and categorized based on recurring themes, such as barriers to adoption, knowledge gaps, and current practices. The findings revealed that the effective communication dynamics, facilitated through both formal channels like agricultural extension services and informal networks among farmers, significantly influence the adaptation processes of cassava farmers in Obio/Akpor by enhancing information sharing and creating supportive environments for innovation. Based on the findings of the study concluded that effective communication dynamics play a pivotal role in the adaptation processes of cassava farmers in Obio/Akpor, facilitating knowledge sharing and fostering a collaborative environment essential for innovation. The study recommended that agricultural stakeholders should enhance the existing communication networks by incorporating both formal and informal channels to ensure that timely and relevant information reaches all farmers, thereby promoting widespread adoption of innovative practices.